KERJA SAMA SELANDIA BARU DENGAN TAIWAN DALAM KERANGKA AGREEMENT BETWEEN NEW ZEALAND AND THE SEPARATE CUSTOMS TERRITORY OF TAIWAN, PENGHU, KINMEN AND MATSU ON ECONOMIC COOPERATION (ANZTEC) - Yanita, Ceni Hardami; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study analyse international trade is carried out by each country to meet the needs of its country and interact with other countries that have similar interests. New Zealand and Taiwan become trading partners and are involved in an international agreement under the auspices of the WTO. This research is interesting to examine seeing the sovereign status of the countries involved in the treaty and the treaty-making process which is slightly different from international treaties in general.This research is a qualitative study that adopts neo liberalism perspective and cooperation theory from Robert O. Keohane and J. Nye. Data for research comes from books, journals, news from the BBC, official NZCIO documents, articles and websites.This study shows that the format of cooperation between New Zealand and Taiwan is made in such a way that it does not endanger trade relations between New Zealand and China, one of which is the use of the nomenclature of the WTO on Taiwan, namely the Separate Customs Territories of Taiwan, Penghu, Kinmen and Matsu as representatives of Taiwan. The signing of ANZTEC provides a very broad market access for trade in goods, services, investment and cultural exchange between New Zealand and Taiwan.Keywords: ANZTEC, New Zealand, Taiwan, China, Cooperation, Trade